2021
DOI: 10.1126/science.abg0879
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the activated human minor spliceosome

Abstract: The minor spliceosome mediates splicing of the rare but essential U12-type pre-mRNA. Here we report the atomic features of the activated human minor spliceosome determined by cryo-electron microscopy at 2.9-Å resolution. The 5′-splice site and branch point sequence of the U12-type intron are recognized by U6atac and U12 small nuclear RNA (snRNA), respectively. Five newly identified proteins stabilize the conformation of the catalytic center. The zinc finger protein SCNM1 functionally mimics the SF3a complex of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
88
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(99 citation statements)
references
References 77 publications
1
88
0
Order By: Relevance
“…This provided a phylogenetic absence/ presence profile that was used in an unbiased genome-wide query for genes with similar phylogenetic profiles (Fig 3A). The resulting list of genes most strongly co-occurring with CENATAC was significantly enriched for components of the minor (U12-dependent) spliceosome complex, including the recently discovered SCNM1 (Bai et al, 2021) (Fig 3B, Table EV2). We thus reasoned that CENATAC may play a role in splicing by the minor spliceosome.…”
Section: Cenatac Is a Novel Component Of The Minor Spliceosomementioning
confidence: 99%
See 1 more Smart Citation
“…This provided a phylogenetic absence/ presence profile that was used in an unbiased genome-wide query for genes with similar phylogenetic profiles (Fig 3A). The resulting list of genes most strongly co-occurring with CENATAC was significantly enriched for components of the minor (U12-dependent) spliceosome complex, including the recently discovered SCNM1 (Bai et al, 2021) (Fig 3B, Table EV2). We thus reasoned that CENATAC may play a role in splicing by the minor spliceosome.…”
Section: Cenatac Is a Novel Component Of The Minor Spliceosomementioning
confidence: 99%
“…B GO term analysis of the genes co-occurring with CENATAC as in (A) with a correlation score of > 0.5. Note: The amount of hits and fold enrichment score were manually changed to accommodate the recently discovered SCNM1 (Bai et al, 2021). Schematics showing key assembly stages in minor intron splicing and minor tri-snRNP assembly: intron recognition (A complex) and the catalytic spliceosome (C complex).…”
Section: A-type Minor Introns Are Spliced Less Efficientlymentioning
confidence: 99%
“…The recent purified structure of the human minor spliceosome revealed six conserved amino acid residues of RBM48 that mediate the interaction of RBM48-ARMC7 protein complex with U6atac 24 . Of these, four amino acid residues are N-terminal to the conserved RRM domain of RBM48.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of in vivo co-expression, Bimolecular Fluorescence Complementation (BiFC), and in vitro pull-down assays showed that maize RBM48 interacts with RGH3 and the core U2 splicing factors U2AF1 and U2AF2 24 . U2AF2 binds to the polypyrimidine tract of U2-type introns; whereas U2AF1 makes contact with the acceptor site 50 .…”
Section: Discussionmentioning
confidence: 99%
“…This ion and its dynamics have now been successfully identified in the major and minor spliceosomes. 16 , 17 …”
mentioning
confidence: 99%